Design of Information System for Satisfaction Level of Airline On Line Ticket Sales with Importance-Performance Analysis Method - Bonie Empy Giri (Sean Institute, 2022)
Demand for aviation services continues to increase each year, it can be seen from the increasing competition among airlines to increase ticket sales on-line. Marketing is one component in the science of Customer Relationship Management. Variety of extra services to entrepreneurs airlines can be seen from a variety of bonus or reward or ease of access in the process of buying and selling tickets so more encouraging entrepreneurs to spur travel or airline ticket sales increase. Under conditions of intense competition, the main thing that should be prioritized by the airline company is the satisfaction of customers or passengers to survive, compete and mengusai market share. which is why the need to do research level user satisfaction tickets on-line services targeting entrepreneurs in accessing the website travel airline with the Importance and Performance Analysis (IPA).